The Application of the EGD Design Process in Environmental Graphic Design for Pasar Baru Jakarta - Laticia Ashila; Putri Dwitasari; Andita Wibyasti Sari Putri; Yosia Enggar Kurniawan (Judikatif: Jurnal Desain Komunikasi Kreatif, 2026)
Pasar Baru Jakarta, a historic commercial district established during the Dutch colonial period, has been officially recognized as a Cultural Heritage Area by the Provincial Government of DKI Jakarta. Despite its significant historical value and multicultural identity, the district currently faces several challenges, including the absence of an integrated wayfinding system, inconsistent visual signage elements, and ineffective communication of its heritage identity to visitors. This study seeks to design an Environmental Graphic Design (EGD) system to support the revitalization program of Pasar Baru Jakarta. This study employs the EGD Design Process proposed by Calori and Vanden-Eynden, which comprises three stages: Pre-Design, Design, and Post-Design. Data collection methods included field observations, visitor interviews, in-depth stakeholder interviews, competitor and comparator studies and expert validation. The findings indicate that the existing EGD elements do not constitute a coherent system owing to the lack of orientation signage, limited interpretive signage, and inconsistent visual standards. Based on these findings, a design concept entitled “Faces of Passer Baroe” was developed, incorporating the heritage architecture, multicultural identity, and colonial visual character of the district into an integrated-signage system. The final outputs encompass identificational, directional, orientation, regulatory, interpretive, and placemaking signage systems, along with an implementation guideline book titled “Passer Baroe: Signage and Wayfinding System Guidelines.” Expert validation confirmed that the design was visually, materially, and technically suitable for implementation in an urban heritage district.